2011
DOI: 10.1038/nrn3027
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of the cognitive model of depression

Abstract: In the 40 years since Aaron Beck first proposed his cognitive model of depression, the elements of this model--biased attention, biased processing, biased thoughts and rumination, biased memory, and dysfunctional attitudes and schemas--have been consistently linked with the onset and maintenance of depression. Although numerous studies have examined the neural mechanisms that underlie the cognitive aspects of depression, their findings have not been integrated with Beck's cognitive model. In this Review, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
1,119
4
31

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,369 publications
(1,236 citation statements)
references
References 118 publications
82
1,119
4
31
Order By: Relevance
“…In various psychiatric disorders, psychosocial stress is a major aetiological factor and excessive fear is a major psychopathology (Cuthbert and Insel, 2013;Disner et al, 2011;Kendler et al, 2003;Kessler, 1997). Mouse CSD resulted in excessive fear learning and memory of an aversive CS-US association, indicating that psychosocial stress induced generalized hyper-reactivity to aversion.…”
Section: A Valid Mouse Model For Psychosocial Stress-induced Hyperactmentioning
confidence: 99%
See 1 more Smart Citation
“…In various psychiatric disorders, psychosocial stress is a major aetiological factor and excessive fear is a major psychopathology (Cuthbert and Insel, 2013;Disner et al, 2011;Kendler et al, 2003;Kessler, 1997). Mouse CSD resulted in excessive fear learning and memory of an aversive CS-US association, indicating that psychosocial stress induced generalized hyper-reactivity to aversion.…”
Section: A Valid Mouse Model For Psychosocial Stress-induced Hyperactmentioning
confidence: 99%
“…Negative valence is a major proposed domain (Cuthbert and Insel, 2013), and includes the excessive fearfulness that is common in MDD and GAD (Disner et al, 2011;Eshel and Roiser, 2010). Importantly, these domains can be studied in humans and other species.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been found that upon encountering negative material the increased activation in limbic regions (e.g., amygdala, hippocampus) is related to a reduced activity in specific regions in the prefrontal cortex (e.g., dorsolateral prefrontal cortex, orbitofrontal cortex, anterior cingulate cortex) with these latter structures being crucial to implement cognitive control over processing of affective material (Davidson et al, 2002;Whittle, Allen, Lubman, & Yucel, 2006). The emerging integrative (gene-by-environment) views on depression allow further exploration of the interplay among genes, neuroendocrine, and stress in relation to multiple cognitive biases (Disner, Beevers, Haigh, & Beck, 2011).…”
Section: Predicting Depressionmentioning
confidence: 99%
“…These observations have been rationalized in terms of altered neurocircuitry proposed to underlie specific depression psychopathologies, e.g. the amygdala -sgACC -PFC circuit for hyper-processing of negative stimuli (Disner et al, 2011). Imaging studies related to specific tasks have been complemented by restingstate (rs) fMRI, which provides information on the synchronicity of spontaneous activity thereby enabling the study of functional connectivity (FC) within and between networks.…”
Section: Introductionmentioning
confidence: 99%